2002
DOI: 10.1590/s0104-66322002000400002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of an industrial wastewater treatment plant using artificial neural networks and principal components analysis

Abstract: -This work presents a way to predict the biochemical oxygen demand (BOD) of the output stream of the biological wastewater treatment plant at RIPASA S/A Celulose e Papel, one of the major pulp and paper plants in Brazil. The best prediction performance is achieved when the data are preprocessed using principal components analysis (PCA) before they are fed to a backpropagated neural network. The influence of input variables is analyzed and satisfactory prediction results are obtained for an optimized situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 20 publications
(19 reference statements)
2
30
0
Order By: Relevance
“…The study also includes Principal Component Analysis, which is a statistical method used to identify the patterns in large data matrices [17] [18] [19]. In this analysis various parameters are considered as vectors in a multi-dimensional space and the vector (direction) in which the largest variance is identified as principal component vector and the vectors are numbered as PC1, PC2 and so on in the order of significance.…”
Section: Discussionmentioning
confidence: 99%
“…The study also includes Principal Component Analysis, which is a statistical method used to identify the patterns in large data matrices [17] [18] [19]. In this analysis various parameters are considered as vectors in a multi-dimensional space and the vector (direction) in which the largest variance is identified as principal component vector and the vectors are numbered as PC1, PC2 and so on in the order of significance.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of the time networks require at least one hidden layer to solve non-linearly separable problems (Oliveira-Esquerre et al, 2002). The number of neurons in this layer was optimized by the Intelligent Problem Solver (IPS) tool of Statistica 7.0 software (StaSoft Inc., 2005), using a sigmoidal activation function.…”
Section: Ann Adjustmentsmentioning
confidence: 99%
“…Theoretical tasks performed in the field have shown that a hidden layer for these models can approximate virtually any complicated and non-linear function (Maier and Dandy, 2005;Cybenko, 1989;Hornik et al, 1989), as proven by experimental and practical results (Homada and Al-Ghusian, 1999;Oliveira-Esquerre et al, 2002).…”
Section: Introductionmentioning
confidence: 99%